The Nature-Climate-Food Nexus: Exploring the Interconnections and Synergies Across Rice Ecosystems, Forests, Wetlands, and Climate Pathways - Kemp, Benjamin; Urfels, Anton; Mirzabaev, Alisher (International Rice Research Institute, 2025)
Rice-based agri-food systems are an integral element of the nature–climate–food nexus: rice is an important staple for over half the global population, anchors global food security, and shapes ecosystems that regulate climate and water. Being sustained by and driving ecological processes, rice cultivation, on one hand, depends on forests that generate rainfall, wetlands that buffer floods and recycle nutrients, and biodiversity that stabilizes yields under stress, while in turn contributing to water storage and regulation, biodiversity habitat provision, and nutrient cycling within these landscapes. Yet these very ecosystems are under mounting pressure from deforestation, wetland loss, and input-intensive farming. Such disruptions weaken hydrological regulation, carbon storage, nutrient cycling, and yield stability that threaten to erode the resilience of rice landscapes. Protecting ecological foundations is therefore essential for safeguarding rice production and nature to meet global goals on food security, climate resilience, and sustainable development. At the same time, rice systems will also need to adjust and align with shifting water and climate conditions to remain resilient.